Comparison of Different Concentrations of Inorganic Trace Minerals in Broiler Diets on Live Performance and Mineral Excretion - Wang, Z.; Cerrate, S.; Yan, F.; Sacakli, P.; Waldroup, P.W. (International Journal of Poultry Science, 2008)
Two consecutive experiments compared different concentrations of inorganic trace minerals in broiler production under different ambient temperature. Both experiments had six treatments, consisting of 100, 80, 60, 40, 20 and 0% of normal trace mineral premix (TMP) inclusion rate with eight and four replicates of sixty male broilers in the first and second experiments, respectively. Experiment 1 began on January 9th and finished on February 20th while Experiment 2 began on July 19th and finished on August 29th. Body weight and feed consumption were determined at 14, 35 and 42 days. At 42nd day two birds per pen were killed and the tibia removed for bone ash determination. In Experiment 2, cohort birds were fed in battery pens from 35 to 37 days. with excreta samples collected for trace mineral analysis. In Experiment 1, birds with no TMP had significantly decreased body weight over all growth periods. Birds fed diets with 20% of normal TMP did not differ in performance from those fed higher levels up to 100% of normal addition rates. There was no difference in any growth variables in Experiment 2 when higher environmental temperatures were in effect. Reduction of TMP in broiler diets could reduce mineral excretion to environment. Levels of Fe, Cu, Mn and Zn in broiler excreta decreased when mineral premix levels were reduced.